Progress in partially degradable titanium-magnesium composites used as biomedical implants - Wang, Jianping; Bao, Zhifan; Wu, Chenliang; Zhang, Song; Wang, Ningwei; Wang, Qiang; Yi, Zhe (Frontiers in Bioengineering and Biotechnology, 2022)
Titanium-magnesium composites have gained increasing attention as a partially degradable biomaterial recently. The titanium-magnesium composite combines the bioactivity of magnesium and the good mechanical properties of titanium. Here, we discuss the limitations of conventional mechanically alloyed titanium-magnesium alloys for bioimplants, in addition we summarize three suitable methods for the preparation of titanium-magnesium composites for bioimplants by melt: infiltration casting, powder metallurgy and hot rotary swaging, with a description of the advantages and disadvantages of all three methods. The titanium-magnesium composites were comprehensively evaluated in terms of mechanical properties and degradation behavior. The feasibility of titanium-magnesium composites as bio-implants was reviewed. In addition, the possible future development of titanium-magnesium composites was discussed. Thus, this review aims to build a conceptual and practical toolkit for the design of titanium-magnesium composites capable of local biodegradation.